Cybersickness Testing Of Gender And Experience Factors Using Virtual Reality - Ancella Hendrika; Clara Theresia; Thedy Yogasara (University of Technology Yogyakarta, 2020)
One of the technologies that people are starting to get interested in is virtual reality (VR). VR is widely used as a means of entertainment, even more so at this time, the e-sports industry is developing rapidly. However, the use of VR can cause cybersickness, a disease arising from sensory and perceptual mismatches between the visual and vestibular systems. The emergence of cybersickness can be related to gender and experience using VR. There have been studies on cybersickness, but the results obtained had not come to the same conclusion. This research aims to identify the effect of gender and experience using VR, predict the timing of cybersickness by using physiological measurements, and provide recommendations that can minimize cybersickness in activities using VR. The measuring instruments used are the galvanic skin response (GSR) and a simulator sickness questionnaire (SSQ). In this study, the influence test is conducted by using ANOVA and Kruskal-Wallis to determine whether gender and experience using VR affect the potential for cybersickness. Based on the GSR measurement results, it found that gender and experiences of using VR do not affect a person's potential for cybersickness. From the result of SSQ measurement, gender does not affect the cybersickness, but the experience of using VR affected a person's potential for cybersickness. Qualitatively, cybersickness symptoms appear in the 15-20 minutes after the VR game has set in. Therefore, it is recommended to limit the usage of VR to less than 15 to 20 minutes per session. Keywords: cybersickness, galvanic skin response (GSR), simulator sickness questionnaire (SSQ), virtual reality